ANALISIS FITUR NEW NORMAL SEBAGAI DISPLAY SHOPEE DALAM MEMBENTUK POLA KONSUMSI PADA MASA COVID-19 - Ivan, Muhammad; Roosdiyana, Shabila Tri; Allyviantoro, Viqhyh (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2021)
The phenomenon of online shopping has become a recent activity in shopping that is in vogue lately. The emergence of various kinds of online shopping platforms has made consumers increasingly have the freedom to make choices. Especially in times of a pandemic, everyone becomes impeded from leaving the house to meet their needs. One of the online shopping applications that focus on this research is the New Normal feature found in the Shoppe application. The theory used in this research is Baudrillard's theory of consumer society, which explains that people consume not only goods but also human services and their relationship with humans. The method used in this research is qualitative with a social construction approach. At this time, the New Normal feature in the Shoppe application plays a significant role in shaping consumer awareness of their needs during the Covid-19 pandemic. This feature also offers the convenience of shopping with low shipping costs and various attractive promos that are offered to be a reason for consumers to consider shopping decisions through the Shopee application.